2023
DOI: 10.1037/law0000353
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trauma education judicial instructions on decisions about complainant credibility in rape trials.

Abstract: Judicial instructions are a practical, but not always effective, way of providing education to jurors to help them evaluate the evidence given by witnesses. In this research, we investigated whether jurors comprehended and applied common judicial instructions intended to help the jury accurately evaluate the evidence given by a rape complainant without being influenced by legally irrelevant stereotypes about the complainant's emotional demeanor. We hypothesized that a trauma education instruction would improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…The evidence relating to judicial directions is not, however, universally positive. Nitschke et al (2022), for example, found that a judicial instruction about the likely effects of trauma on witness testimony resulted in jurors rating all complainer testimony as less credible, regardless of the degree of emotion the complainer displayed. The authors speculate that this was because the instruction left jurors uncertain about how they should evaluate credibility, resulting in a general scepticism towards the witness.…”
Section: Where To Next? Future Directions For the Role Of Demeanour I...mentioning
confidence: 99%
“…The evidence relating to judicial directions is not, however, universally positive. Nitschke et al (2022), for example, found that a judicial instruction about the likely effects of trauma on witness testimony resulted in jurors rating all complainer testimony as less credible, regardless of the degree of emotion the complainer displayed. The authors speculate that this was because the instruction left jurors uncertain about how they should evaluate credibility, resulting in a general scepticism towards the witness.…”
Section: Where To Next? Future Directions For the Role Of Demeanour I...mentioning
confidence: 99%